Coexistence of Kondo effect and non trivial Berry phase in Gd doped Bi2Se3: an ARPES and magneto-transport study - Ghosh S.; Singh R.; Dixit S.; Kumar S.; Kumar Y.; Shimada K.; Kumar Ghosh A.; Lakhani A.; Chatterjee S. (My University, 2025)
The presence of magnetic impurities in topological insulators can disrupt their time reversal symmetry and lead to the emergence of an energy gap. This study delves into the energy band structure and the Kondo effect through the introduction of Gadolinium (Gd) magnetic perturbations (at levels of x = 0.1 , 0.16 ) into a pure Bi2Se3 single crystal. In the case of the Bi1.9Gd0.1Se3 (5%) single crystal, the Kondo effect becomes observable at temperatures below 50 K. However, the unaltered parent and Bi1.84Gd0.16Se3 (8%) exhibit typical metallic behavior. The pure sample displays the highest magnetoresistance (MR) of around 225% and demonstrates quantum oscillations driven by a nontrivial berry phase. The sample doped with 5% Gd undergoes a transition from negative MR to positive MR due to a presence of mixed magnetic state resulting from the opening of a gap at the Dirac point. This gap opening is confirmed through angle-resolved photoemission spectroscopy (ARPES) measurements. The comparison of the parameters obtained from the SdH and ARPES measurements, the reduction in the k F values in the magnetotransport measurements is likely due to the band bending induced by the Schottky barrier. Thermoelectric properties are assessed across all prepared samples. The undoped sample displays the highest Seebeck coefficient and power factor values of − 398.02 μ V K − 1 and 6.83 mW mK − 2 , respectively, at room temperature. These values are notably high for thermoelectric applications at room temperature. © 2025 IOP Publishing Ltd. All rights, including for text and data mining, AI training, and similar technologies, are reserved.